On nonlinear spectra for some nonlocal boundary value problems - Sergejeva, Natalija (Mathematical Modelling and Analysis, 2008)
We consider a second order nonlinear differential equation with nonlocal (integral) condition. The spectrum of it differs essentially from the known ones.First Published Online: 14 Oct 2010